2018
DOI: 10.1039/c7bm00649g
|View full text |Cite
|
Sign up to set email alerts
|

The role of hierarchical design and morphology in the mechanical response of diatom-inspired structures via simulation

Abstract: Diatoms are microscopic algae with intricate shell morphologies and features ranging from the nanometer to the micrometer scale, which have been proposed as templates for drug delivery carriers, optical devices, and metamaterials design. Several studies have found that diatom shells show unique mechanical properties such as high specific strength and resilience. One hypothesis is that these properties stem from the structural arrangement of the material at the nanometer and micrometer length scales, challengin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…It is well known that diatom frustules, regardless of the species, have hierarchical pore structures . The hierarchical pore structures of the Coscinodiscus species ( C .…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that diatom frustules, regardless of the species, have hierarchical pore structures . The hierarchical pore structures of the Coscinodiscus species ( C .…”
Section: Resultsmentioning
confidence: 99%
“…The main objective of our research is to explore diatom's potential for MEMS, namely, oscillators or vibrational sensors able to resonate at eigenfrequencies detecting specific external vibration. Our scientific group recently managed to make other steps towards this goal, namely, to achieve guided colonization of Si wafers with diatoms [21] and to reduce natural diatom opal to obtain nanostructured Si objects while retaining neat nanostructure [22]. These steps are being theoretically and conceptually supported by the modelling presented in this manuscript.…”
Section: Introductionmentioning
confidence: 83%
“…Moreno et al studied the relationship between porosity and mechanical properties [21]. Similarly, Gutiérrez et al investigated the effect of morphological features (such as the diameter of diatoms, pore size and thickness of individual walls) on the deformation response of centric diatoms [22]. It remains extremely challenging, if not impossible to simulate the real structure of diatoms.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical behavior of frustules was studied using micro-and nanomechanical testing as well as finite element analysis (FEA) [27][28][29][30][31]. Atomic force microscopy (AFM) nanoindentation measurements of frustules revealed that Young's modulus and hardness values are varying significantly, from 7 to hundreds of GPa, and from 1 to 12 GPa, respectively, depending on the location where the measurement was performed [27,32].…”
Section: Introductionmentioning
confidence: 99%
“…These findings support that the mechanical performance is not only related to the amorphous bio silica itself but also to the hierarchical 3D morphology of porous exoskeleton structures at the nano, submicrometer to micrometer scales of the frustule. FEA is a favored approach to study mechanical properties of biomaterials, especially to understand complex hierarchical 3D porous structures [12,19,22,28,29]. In the FEM framework, the general approach is to simplify the geometry to reduce computational efforts and to increase the likelihood of convergence of the numerical model.…”
Section: Introductionmentioning
confidence: 99%